Active Liver Bleed Caught During FAST Exam from Spontaneous Hemangioma Rupture: A Case Report - Raul Rodriguez; Nicole Aviles (Clinical Practice and Cases in Emergency Medicine)
Introduction: This case highlights the advances that have been made when skilled sonographers using point-of-care ultrasound (POCUS) are able to evaluate for more than free fluid on the focused assessment with sonography in trauma (FAST) exam. Specific solid organ injury including an active liver bleed can also be detected during FAST exam, as seen in this case of a unstable hypotensive patient. Case Report: A 55-year-old male who had recently been admitted to trauma service due to multiple rib fractures presented back to the emergency department (ED) due to an episode of syncope and was found to have an acute, left segmental pulmonary embolism. The patient was started on anticoagulation, and the following day was found to be hypotensive, encephalopathic, and minimally responsive to verbal stimuli. During the resuscitative efforts, a FAST exam performed by the emergency physician showed grossly positive free fluid in various quadrants and active flow around the liver concerning for active bleeding. Computed tomography subsequently confirmed an active subcapsular bleed of the liver, and patient was taken emergently to surgery for hemostasis from a ruptured liver hemangioma. This was then followed by a right hepatic arterial embolization. Conclusion: While the FAST exam is well established in the setting of trauma, this case further highlights the use of POCUS in a patient with undifferentiated hypotension and shock. It serves as a reminder of how imperative it is to not anchor on the primary diagnosis and reinforces the importance of ultrasonographic competency in physicians of all specialties and not just those in the realm of emergency medicine and critical care.